Business english speaking : advanced masterclass - Roche, Marc, ....- (Michigan : Independently Published, 2019)
Business English Speaking: Advanced Masterclass - Speak Advanced ESL Business English with Confidence & Elegance: Business Meetings & Presentations in English. Includes 300+ PPT Presentation Templates.American & British Business English Advanced Speaking for ESL Students and Teachers. This business English book provides a solid framework for English language learners to acquire advanced Business English Speaking skills by exploring the secret psychology and dynamics behind effective business communication in English, together with advanced phrases and self-study exercises to improve business vocabulary and confidence. This book is ideal for any business setting where the person has to speak in one-to-one or group interactions, like meetings, presentations, parties and other public speaking events. With this business English communication course, you will learn: -How to speak ESL Business English with Confidence & Elegance. You will learn: -How to deliver outstanding presentations-How to hold a successful meeting in English -How to excel at public speaking -How to maximize your influence in ANY professional situation in English To make this self-study Business English Speaking course even more effective, it includes 300+ Premium Business Presentation Templates in PowerPoint format that you can download whenever you like.
Keywords: bedrijfsjargon; engels